К фауне кровососущих комаров Донецкой области - Рязанцева, А.Е. (Вестник зоологии, 1971)
The article is based on the investigations carried out in the territory of the Donetsk region. 24 species of midge s belonging to four genera are found. Aedes annulipes Me i g.. A. cyprius Ludl. , A. excrucians Walk. , A. cantans Meig. , Culex pipiens molestus F о г s k are the mass species.